Discussion on the concepts of "coordination" and "agility" in terms of physical education - Zaporozhanov, V.A.; Boraczynski, Tomasz (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
In the scientific and methodological literature and practice of physical education concepts of "coordination" and "agility" are often used synonymously. And discussion about the appropriateness distinguish these concepts is mainly analytical character. Purpose : to evaluate the nature of the relationship metrically between indicators kinesthesia (which characterize the internal processes of interaction in the neuro-muscular system - coordination) and the efficient delivery of a complex exercise (in cooperation man in the external environment of physical education - agility). Material : 77 students surveyed. Students performed on 100 strikes the ball into the goal in terms of golf (10 control measurements). The experiment was conducted for 8 months. 7700 measurement precision of centimeters processed statistically. Calculated reliability of measurements: 100 comparability repetitive beats, accuracy hitting the ball into the goal and the pace of learning in terms of the impact of blows. Results : the total volume measurements was characterized by high variability (V% = 53,5), indicating that the low status of kinesthesia surveyed. This reduces the reliability of the correlation coefficients according to 30 and then 10 of the best students in the general rank in terms of reliability of measurements. Significant correlation occurred only in terms of performance beats the purpose of learning the technique and pace (0,417; n = 30, p <0,05; and 0,677; n = 10, p <0,05). Conclusions : Overall, the results of our study showed that the concept of "coordination" and "agility" should still be distinguished. In some cases, students with a good level of kinesthesia occurred and high mobility in complex locomotion. If we recognize it expedient to continue this discussion, then we must rely on objective, metric information. This information should be obtained in studies with a broad contingent surveyed, consistently show good concentration and high reliability results in a series of repeated measurements.